RAISING INFORMATION AND COMMUNICATION TECHNOLOGIES COMPETENCE OF SCIENTIFIC AND PEDAGOGICAL EMPLOYEES - A KEY REQUIREMENT OF THE QUALITY OF EDUCATIONAL PROCESS - Nataliia V. Morze; Oksana P. Buinytska (Інформаційні технології і засоби навчання, 2017)
In the article it was analyzed one of the basic conditions of providing the quality of higher education according to the system of internal quality assurance standards ESG (European quality assurance standards and guidelines) to increase the ICT competence of scientific-pedagogical staff of the University. It was described the modular system of training for scientific and pedagogical staff of the Borys Grinchenko Kyiv University. Special attention is paid to the description of the system of raising the level of formation the ICT competence as one of the key competences of the modern teacher. The system of professional development, which is based on creating mixed studying and technology of "flipped classroom", formative assessment, innovative educational and ICT technologies according to the specially designed informative module "Informational and communication technologies", which allows scientific-pedagogical staff to use modern ICT and educational technologies effectively for their further applying in the provision of educational services and the development of quality of open educational content and open educational e-environment available to the student at any convenient time, which will significantly improve the quality of the educational process.